Locally led adaptation: drivers for appropriate grassroots initiatives. Issue 2 (1st February 2021) - Westoby, Ross; Clissold, Rachel; McNamara, Karen E.; Ahmed, Istiakh; Resurrección, Bernadette P.; Fernando, Nishara; Huq, Saleemul
ABSTRACT: Adapting to the impacts of climate change is one of the most urgent priorities of our time. Given that the impacts of climate change are experienced at local scales, it makes sense that adaptation should occur locally, and yet, despite this, locals often have little control over how adaptation is funded, designed and delivered in order to climate-proof their places and futures. Increasingly competitive access to funding and limited progress towards sustainable adaptation outcomes prompts our call to rethink adaptation at the local scale. Drawing from grounded research with locals, we explore three case examples from the Asia-Pacific region, ranging from the coastal belt of Bangladesh, to a peri-urban informal settlement in the Philippines, and to a small rural island in Vanuatu. These examples help illustrate how locally led adaptation (LLA) gives us hope for more equitable, effective and sustainable adaptation outcomes. We show how LLA can help to reduce dependency and support local autonomy, diverse capabilities and creativity. We propose nine mutually reinforcing drivers of LLA to improve grassroots initiatives. These drivers focus on locally led decision-making, local strengths and resources (e.g. institutions, social networks, local knowledge and coping mechanisms), local realities, local vulnerability contexts and inequalities, local metrics for measuring "success", and local agendas which should be supported or enabled by external agencies. These drivers support local people to determine their own adaptation futures and ensure finite funding resources are utilised in meaningful ways.